RNA Polymerase: Step by Step Kinetics and Mechanism of Transcription Initiation - Henderson, Kate L. (Biochemistry, 2019)
To determine the step-by-step kinetics and mechanism of transcription initiation and escape by E. coli RNA polymerase from the λPR promoter, we quantify the accumulation and decay of transient short RNA intermediates on the pathway to promoter escape and full-length (FL) RNA synthesis over a wide range of NTP concentrations by rapid-quench mixing and phosphorimager analysis of gel separations. Experiments are performed at 19 °C, where almost all short RNAs detected are intermediates in FL-RNA synthesis by productive complexes or end-products in non-productive (stalled) initiation complexes, and not from abortive initiation. Analysis of productive-initiation kinetic data yields composite second-order rate constants for all steps of NTP binding and hybrid extension up to the escape point (11-mer). The largest of these rate constants is for incorporation of UTP into the dinucleotide pppApU in a step which does not involve DNA opening or translocation. Subsequent steps, each of which begins with reversible translocation and DNA opening, are slower with rate constants that vary more than ten-fold, interpreted as effects of translocation stress on the translocation equilibrium constant. Rate constants for synthesis of 4-and 5-mer, 7-mer to 9-mer and 11-mer are particularly small, indicating that RNAP-promoter interactions are disrupted in these steps. These reductions in rate constants are consistent with the previously-determined 9 kcal cost of escape from λPR. Structural modeling and previous results indicate that the three groups of small rate constants correspond to sequential disruption of in-cleft, −10 and −35 interactions. Parallels to escape by T7 RNAP are discussed.